PROFILE OF VICTIMS OF SEXUAL VIOLENCE CASES AGAINST WOMEN EXAMINED AT THE HOSPITAL. Dr.PIRNGADI MEDAN PERIOD JANUARY 2021 TO JUNE 2023 - Sidauruk, Horas Ahmad; Sitepu, Agustinus; Marbun, Doaris Ingrid; Petrus, Asan; Lubis, Adriansyah (Jurnal Forensik dan Medikolegal Indonesia, 2024)
Background: Forms of violence against women include physical, sexual, economic, political, and psychological violence that can be carried out by individuals, communities, and the state. The types of sexual violence that can occur are crimes, sexual violence (sexual violance) and obscenity. The purpose of this study is "Knowing the profile of victims of sexual violence cases against women examined at the hospital Dr.Pirngadi Medan for the period January 2021 to June 2023. Method: This study was conducted by collecting data using secondary data, all medical records of sexual violence against women examined at the Emergency Department of the Hospital. Dr. Pirngadi Medan on Cases of Sexual Violence Against Women in the period January 2021 to June 2023 and the data listed variables that will be studied in accordance with the specific objectives of this study. Results: The number of cases of sexual violence against women examined at Dr. Pirngadi Medan Hospital from January 2021 to June 2023 was 610 victims. The highest number of cases of sexual violence based on age was in the age group of adolescents 12-25 years as many as 508 victims with a percentage of 83.3%. The number of women who experienced cases of sexual violence based on marital status, as many as 599 victims, namely with unmarried status, with a percentage of 98.2%, and the lowest as many as 11 victims, namely with marital status with a percentage of 1.8%. K